Analisis Semiotik Upa-upa dalam Tradisi Lisan Manyonggot–Nyonggoti di Tapanuli Selatan - Ramnaega L Siregar; Rosmawaty Harahap; Elly Prihasti Wuriyani (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
The presence of a child is a dream for every married couple. The presence of a child in the family is a complement to happiness. In welcoming this happiness, many traditional events are held in each region. In South Tapanuli, the welcome ceremony is an oral tradition that is usually carried out. This manyonggot-ngonggoti event is usually carried out by the family of the woman. Manyonggot-nyonggoti aims to provide prayers and strength for prospective mothers and their unborn babies. In this ritual, a lot of equipment is needed. Both from food and tools. All these ingredients are united in a medium called upa - upa. These food ingredients are arranged in such a way to be enjoyed by the mother-to-be and her baby-to-be. Upa - upa has the meaning of each symbol. These symbols of food ingredients have their own meaning to be given to the mother-to-be and her baby. Some symbols of food ingredients in this ceremony are eggs, goldfish, salt and many others. To find out the meaning of each symbol, a semiotic analysis was carried out. The data is taken from the results of interviews with several traditional leaders and literacy from several references.